Modification of estimate standards for pricing in construction - N.M. Levchenko (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2022)
The article states that over the years of independence, the construction industry has gone through a thorny path of trial and error, since at the initial stages of its formation, construction organizations did not have sufficient knowledge and practical skills, they worked according to old, still Soviet standards. At present, the experience of Ukrainian builders is much greater, enriched by the new Estimated Norms of Ukraine in the form of two Guidelines – “Guidelines for determining the cost of construction” and “Guidelines for determining the cost of design, scientific design, survey work and examination of design documentation for construction”. However, despite this, the issues of the procedure for accounting for the cost of construction products or construction work of transaction costs still remain unresolved in construction practice, which significantly complicates the pricing procedure in construction. For a clear understanding of the essence of the concept of “transaction costs”, its interpretation in the reference literature and among scientists is considered. It is stated that a theoretical consensus on the issue, which in fact is transaction costs, has not yet been reached. The author's definition of traction costs is proposed as costs associated with the organization of interaction and coordination of relationships between business entities, which are aimed at creating conditions for the effective conduct of economic activities and provide for a decrease in economic benefits due to the disposal of assets or hidden losses, as a result of the opacity of the economic environment and the asymmetry of market information, or an increase in the obligations associated with the maintenance of the business partnership process. The necessity of making additions and adjustments to the Estimated Standards of Ukraine “Guidelines for determining the cost of construction” in terms of establishing standards for transaction costs for construction projects is proved. Clearly formulated proposals for the modification of estimated standards for pricing in construction, the implementation of which in practice will allow: to determine a more realistic cost of construction and construction work; ensure strict control over the targeted use of funds allocated to finance construction projects, as well as introduce a set of effective measures to maintain an adequate state construction policy, supported by effective institutions for regulating the activities of contractors in the construction sector.